Implementasi Pembelajaran IPS berbasis Green Consumer untuk Meningkatkan Keterampilan Berfikir Kritis Peserta Didik - Novidya Yulanda; Vella Anggresta (INTELEKTIUM, 2024)
Climate change and its serious impacts are a global concern. Overconsumption and environmental pollution are among the main factors. The green consumers movement is emerging as a solution. Social studies education plays an important role in instilling environmental values and developing critical thinking skills in students. This article discusses the link between green consumers, social studies learning, and critical thinking skills. The findings state that developing critical thinking skills through social studies learning will help students become more effective agents of change in efforts to preserve the earth and increase green consumer awareness in students. Social studies learning also plays an important role in developing various intellectual dimensions of students, such as linguistic, logical-mathematical, spatial, social, and personal intelligence. Social studies learning plays an important role in preparing a smart, critical and creative young generation to face climate change and build a sustainable future.